2017
DOI: 10.3390/su9071205
|View full text |Cite
|
Sign up to set email alerts
|

Inclusive Nature-Based Solutions for Urban Regeneration in a Natural Disaster Vulnerability Context: A Case Study of Chongqing, China

Abstract: Currently, economic development has become a dominant factor in the promotion of urban regeneration in China. This means that decision makers often overlook the impacts on the natural environment when planning urban regeneration within a region. To properly face such challenges and others that may arise, a strategy relying on Nature-Based Solutions (NBS) can enhance the physical and ecological environment of a city, while ensuring greater resilience to natural disasters, and the use of fewer resources. NBS als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“…Considering the pressures of economic, spatial, and social sprawl on climate change adaptability in these districts, administrators in regions prone to this type of development should emphasize industries including modern services, information technology, and the arts and culture in order to maintain coordinated development between USS and CCA [49,51]. At the same time, these districts should also apply the advanced technology of NBS (Nature-Based Solutions) to address development issues, such as the restoration of urban swampy peatlands, construction of "green roofs", and removal of all buildings in ventilation corridors [52]. For example, swamp peatlands are an important carbon sink source.…”
Section: Spatial Difference Analysis Of Coordinated Degree Of Uss Andmentioning
confidence: 99%
See 3 more Smart Citations
“…Considering the pressures of economic, spatial, and social sprawl on climate change adaptability in these districts, administrators in regions prone to this type of development should emphasize industries including modern services, information technology, and the arts and culture in order to maintain coordinated development between USS and CCA [49,51]. At the same time, these districts should also apply the advanced technology of NBS (Nature-Based Solutions) to address development issues, such as the restoration of urban swampy peatlands, construction of "green roofs", and removal of all buildings in ventilation corridors [52]. For example, swamp peatlands are an important carbon sink source.…”
Section: Spatial Difference Analysis Of Coordinated Degree Of Uss Andmentioning
confidence: 99%
“…To improve climate change adaptability, policymakers in each district could employ NBS to promote syngergies between urban-climate systems. NBS makes urban environments more sustainable and less resource-consuming [52]. In addition, NBS can also improve the social well-being of residents and may create more inclusive and engaged communities [52].…”
Section: Moderately Coordinated Development With Lagging Ccamentioning
confidence: 99%
See 2 more Smart Citations
“…They concluded that the bootstrap DEA model was highly utilized as a benchmarking technology in later studies. Xiang et al (2017) [23] used the DEA models in a variety of studies, including research on nature-based alternatives for urban regeneration related to China's vulnerability to natural disasters. In addition, Biondi et al (2013) [24] used the DEA model to assess corporate efficiency by assessing the efficiency of car dealers in the automotive industry, and Ohe (2016) [25] used the window DEA model to analyze the efficiency of Japanese hotels by size and region.…”
Section: Concept Of Deamentioning
confidence: 99%